2010
DOI: 10.1269/jrr.09114
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Proteins Indicating Radiation-induced Hepatic Toxicity in Cirrhotic Rats

Abstract: Radiation therapy (RT) has been emerging as one of the palliative treatments for locally advanced hepatocellular carcinoma (HCC). However, hepatic toxicity is a major obstacle in radiotherapy for HCC. The purpose of this study is to identify proteins indicating radiation-induced hepatic toxicity in cirrhotic rats, which can be used as possible biomarkers. Liver cirrhosis was induced in Wistar rats with thioacetamide (TAA) 0.3 g/L in drinking water for 9 weeks. The development of liver cirrhosis was observed hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Consequently, many studies have been designed using rat models to elucidate the histopathological changes that occur following liver irradiation [16, 17, 1922]. Liver irradiation generally results in a loss of parenchymal hepatocytes and distortion of lobular architecture accompanied by pericentral and periportal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, many studies have been designed using rat models to elucidate the histopathological changes that occur following liver irradiation [16, 17, 1922]. Liver irradiation generally results in a loss of parenchymal hepatocytes and distortion of lobular architecture accompanied by pericentral and periportal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the process of angiogenesis in liver disease is associated with the development of fibrosis [25]. Given that ionizing radiation causes liver fibrosis [26], there is a possibility that ionizing radiation-induced angiogenesis by HHSECs may be involved in the radiation-induced liver damage. Additionally, ionizing radiation is known to induce the expression of diverse genes that play key roles in cell growth and immune responses, including interleukin-6 (IL-6), basic fibroblast growth factor (bFGF) and platelet-derived growth factor (PDGF), in various types of normal endothelial cell lines [27, 28].…”
Section: Discussionmentioning
confidence: 99%
“…They found that the tumor response improved with increased radiation dose, but complications arising from increased RT doses were also observed. Radiation dose to the normal liver was a limiting factor in dose escalation; hepatic toxicity is a major obstacle in radiotherapy for HCC [30]. …”
Section: Discussionmentioning
confidence: 99%